Inoculum production of Phytophthora medicaginis can be used to screen for partial resistance in chickpea genotypes - Bithell, Sean L.; Drenth, Andre; Backhouse, David; Harden, Steve; Hobson, Kristy (Frontiers in Plant Science, 2023)
Phytophthora root rot caused by Phytophthora medicaginis is an important disease of chickpea (Cicer arietinum) in Australia with limited management options increasing reliance on breeding for improved levels of genetic resistance. Resistance based on chickpea-Cicer echinospermum crosses is partial with a quantitative genetic basis provided by C. echinospermum and some disease tolerance traits originating from C. arietinum germplasm. Partial resistance is hypothesised to reduce pathogen proliferation, while tolerant germplasm may contribute some fitness traits, such as an ability to maintain yield despite pathogen proliferation. To test these hypotheses we used P. medicaginis DNA concentrations in the soil as a parameter for pathogen proliferation and disease assessments on lines of two recombinant inbred populations of chickpea-C. echinospermum crosses to compare the reactions of selected recombinant inbred lines and parents. Our results showed reduced inoculum production in a C. echinospermum backcross parent relative to the C. arietinum variety Yorker. Recombinant inbred lines with consistent low levels of foliage symptoms had significantly lower levels of soil inoculum compared to lines with high levels of visible foliage symptoms. In a separate experiment a set of superior recombinant inbred lines with consistently low levels of foliage symptoms were tested for soil inoculum reactions relative to control normalised yield loss. The in-crop P. medicaginis soil inoculum concentrations across genotypes were significantly and positively related to yield loss, indicating a partial resistance-tolerance spectrum. Disease incidence and the rankings for in-crop soil inoculum were correlated strongly to yield loss. These results indicate that soil inoculum reactions may be useful to identify genotypes with high levels of partial resistance.